Rabies and distemper outbreaks in smallest Ethiopian wolf population. - Marino, J; Sillero-Zubiri, C; Deressa, A; Bedin, E; Bitewa, A; Lema, F; Rskay, G; Banyard, A; Fooks, A (Centers for Disease Control and Prevention, 2017)
Widespread deaths recently devastated the smallest known population of Ethiopian wolves. Of 7 carcasses found, all 3 tested were positive for rabies. Two wolves were subsequently vaccinated for rabies; 1 of these later died from canine distemper. Only 2 of a known population of 13 wolves survived.